Uncertainty Response Scale: The Assessment Tool for Adolescent Interaction with Multidimensional Stress - M.A. Odintsova; N.P. Radchikova; M.G. Sorokova (Клиническая и специальная психология)
The adaptation of the Uncertainty Response Scale (URS) aimed at studying the ways in which adolescents interact with uncertainty stress situations is described. The scale contains 25 questions and includes three subscales: “Emotional uncertainty,” “Cognitive uncertainty,” and “Desire for change”. The questionnaire has good internal consistency (Cronbach’s alpha for scales 0.85-0.93; CFI=0.93; TLI=0.92; RMSEA=0.060 [0.057; 0.062]; SRMR=0.06) in a sample of adolescents from different regions of the Russian Federation (N=1718; age from 12 to 18 years; average age 14±1 years; 53.8% female). The URS validity is confirmed by the expected correlations with the scales of the “Multidimensional Students’ Life Satisfaction Scale” and “Multidimensional School Engagement Scale”. The validity is also supported by the fact that the URS allows to differentiate respondents in different stressful situations: if a teenager finds himself in a maximally stressful situation, emotional reactions to uncertainty increase, while cognitive reactions to uncertainty are quite stable, and readiness for change decreases. The “Response to Uncertainty Scale” can be used to conduct large-scale longitudinal studies, studies of adolescents from different groups, including vulnerable groups, as well as individual studies to build subsequent practice of psychological assistance.